Analysis Of The Fulfillment Of Teacher Standards In Public Junior High Schools In Gorontalo City - Nopo, Moh. Alfathir; Arwildayanto, Arwildayanto; Arifin, Arifin (Sustainable Human Capital Development Journal, 2025)
The purpose of this study was to analyze: (1) the level of fulfillment of educator competency standards in public junior high schools in Gorontalo City, (2) the level of fulfillment of educators’ academic standards in public junior high schools in Gorontalo City, (3) the level of fulfillment of academic standards according to educators’ field of duty in public junior high schools in Gorontalo City, and (4) the level of fulfillment of certification academic standards relevant to educators’ scientific field in public junior high schools in Gorontalo City.This study employed a quantitative approach with a descriptive research design. The subjects of this study were teachers, with a total sample of 221 participants. Data were collected through questionnaires, observation, and documentation. The data analysis technique used in this study was descriptive quantitative analysis in the form of percentages.The results of this study indicate that: (1) the level of fulfillment of educator competency standards is in the good category with a percentage of 84.46%; (2) the level of fulfillment of educators’ academic standards is in the good category with a percentage of 82.7%; (3) the level of fulfillment of academic standards according to educators’ field of duty is in the good category with a percentage of 81%; and (4) the level of fulfillment of certification academic standards relevant to educators’ scientific field is in the good category with a percentage of 88%.